If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) = 24 Reorder the terms: 2(-1 + x) = 24 (-1 * 2 + x * 2) = 24 (-2 + 2x) = 24 Solving -2 + 2x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 24 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 24 + 2 2x = 24 + 2 Combine like terms: 24 + 2 = 26 2x = 26 Divide each side by '2'. x = 13 Simplifying x = 13
| 93=-6x+3(-2x-13) | | 8x-12+7=-3 | | 3x^2+30x-4=0 | | 4x+11=10x-7 | | z+5=-5 | | 4(3x-5)+x=z | | 11y-12=6y+8 | | 6y+4=2y+20 | | 5xa+7=c+a | | 4(3x-5)+x= | | 10x+5(z-12)=0 | | -3x-10=-2x+4 | | 0.6(j-2)=0.3l | | 20+x=2(20-2x) | | 14-d=45 | | x+2x+2x-30=5400 | | 8-n-3n=6 | | -6x+2y=5 | | 6x-2(-6x+3)=120 | | 2x+20=-3x+50 | | 4(x-3)+7=-3 | | 7x+2(3x+7)=144 | | 6x^2+9x-4=38 | | ax^3+bx-5=0 | | D+8=-7 | | -4(n-b)=12 | | 9(n+6)-5(2+2n)=-8n+5n | | 5(x+4)+14=59 | | 21=3(c-9) | | 6x-2(-6+3)=120 | | 3a+3b+3c=3b | | 7x-2-3x=-10 |